Foxp3 Molecular Dynamics in Treg in Juvenile Idiopathic Arthritis - Copland, Alastair; Bending, David (Frontiers in Immunology, 2018)
Since the identification of the regulatory T-cell (Treg)-associated transcription factor Foxp3, there have been intensive research efforts to understand its biology and roles in maintaining immune homeostasis. It is well established that thymic selection of a repertoire of self-reactive Foxp3+ T-cells provides an essential mechanism to minimise reactions to self-antigens in the periphery, and thus aid in the prevention of autoimmunity. It is clear from both genetic and immunological analyses of juvenile idiopathic arthritis (JIA) patients that T-cells have a strong role to play in both the initiation and propagation of disease. The current paradigm is to view autoimmunity as a consequence of an imbalance between inflammatory and immunoregulatory mechanisms. This view has led to the assigning of cells and inflammatory mediators to different classes based on their assumed pro- or anti-inflammatory roles. This is typically reported as ratios of effector T-cells to Treg cells. Problematically, many analyses are based on static ‘snapshots-in-time’, even though both mouse models and human patient studies have highlighted the dynamic nature of Foxp3+ T-cells in vivo, which can exhibit plasticity and time-dependent functional states. In this review, we discuss the role of Foxp3 dynamics in the control of T-cell responses in childhood arthritis, by reviewing evidence in humans and relevant mouse models of inflammatory disease. Whilst the cellular dynamics of Treg have been well evaluatedleading to standard data outputs such as frequency, quantity and quality (often assessed by in vitro suppressive capacity) we discuss how recent insights into the molecular dynamics of Foxp3 transcription and its posttranslational control may open up tantalising new avenues for immunotherapies to treat autoimmune arthritis.